Development of fluorescent Plasmodium falciparum for in vitro growth inhibition assays - Wilson, Danny W (BioMed Central, 2010)
BACKGROUND: Plasmodium falciparum in vitro growth inhibition assays are widely used to evaluate and quantify the functional activity of acquired and vaccine-induced antibodies and the anti-malarial activity of known drugs and novel compounds. However, several constraints have limited the use of these assays in large-scale population studies, vaccine trials and compound screening for drug discovery and development. METHODS: The D10 P. falciparum line was transfected to express green fluorescent protein (GFP). In vitro growth inhibition assays were performed over one or two cycles of P. falciparum asexual replication using inhibitory polyclonal antibodies raised in rabbits, an inhibitory monoclonal antibody, human serum samples, and anti-malarials. Parasitaemia was evaluated by microscopy and flow cytometry. RESULTS: Transfected parasites expressed GFP throughout all asexual stages and were clearly detectable by flow cytometry and fluorescence microscopy. Measurement of parasite growth inhibition was the same when determined by detection of GFP fluorescence or staining with ethidium bromide. There was no difference in the inhibitory activity of samples when tested against the transfected parasites compared to the parental line. The level of fluorescence of GFP-expressing parasites increased throughout the course of asexual development. Among ring-stages, GFP-fluorescent parasites were readily separated from uninfected erythrocytes by flow cytometry, whereas this was less clear using ethidium bromide staining. Inhibition by serum and antibody samples was consistently higher when tested over two cycles of growth compared to one, and when using a 1 in 10 sample dilution compared to 1 in 20, but there was no difference detected when using a different starting parasitaemia to set-up growth assays. Flow cytometry based measurements of parasitaemia proved more reproducible than microscopy counts. CONCLUSIONS: Flow cytometry based assays using GFP-fluorescent parasites proved sensitive and highly reproducible for quantifying the growth-inhibitory activity of antibodies and anti-malarials, with superior reproducibility to light microscopy, and are suitable for high-throughput applications.